2007
DOI: 10.1021/jo062305n
|View full text |Cite
|
Sign up to set email alerts
|

A New Route to Highly Functionalized Heterocyclic Rings

Abstract: A novel cascade reaction has been developed for the rapid construction of heterocyclic rings. The cyclization is thermally induced and does not involve the use of metal ions. This highly efficient construction of furans has been developed during studies directed toward the synthesis of the antibiotic lactonamycin 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…An analogous diradical mechanism was proposed by Parsons et al to account for an interesting cyclization of enediynes discovered in their laboratory. xvi More recently, Ley and coworkers have reported the cyclotrimerization of triyne 22 carried out in DMF either by heating at 200 °C or by using focused microwave heating xvii. Ley et al reported the isolation of an intermediate that they identified as 27 , leading to the proposal of the mechanism outlined in Scheme 3 involving several unusual strained and reactive intermediates.…”
mentioning
confidence: 99%
“…An analogous diradical mechanism was proposed by Parsons et al to account for an interesting cyclization of enediynes discovered in their laboratory. xvi More recently, Ley and coworkers have reported the cyclotrimerization of triyne 22 carried out in DMF either by heating at 200 °C or by using focused microwave heating xvii. Ley et al reported the isolation of an intermediate that they identified as 27 , leading to the proposal of the mechanism outlined in Scheme 3 involving several unusual strained and reactive intermediates.…”
mentioning
confidence: 99%
“…Such reactions have allowed new architectures to be synthesised, as well as providing more concise syntheses of biologically important molecules and natural products in general. Cascade sequences can proceed by invoking a number of mechanisms including thermal, photochemical, radical, metal‐catalysed and organocatalysis …”
Section: Methodsmentioning
confidence: 99%
“…Parsons and co‐workers have demonstrated that a thermal intramolecular cyclisation can be used to form the lactonamycin core and other interesting fused heterocyclic and carbocyclic compounds without the use of metal catalysis . Further, it was found that in general, ene‐diynes can cyclise to afford furans and dihydrofurans …”
Section: Methodsmentioning
confidence: 99%
“…3-(Trimethylsilyl)propynoic acid amides are valuable intermediates in the synthesis of biologically important heterocyclic compounds, such as chiral 2-trimethylsilyldihydro-1,3-oxazoles [1], trimethylsilylidenehydantoins [2], 1,5-trisubstituted 1H-1,2,3-triazoles [3], indoloquinolines [key compounds in the total synthesis of alkaloids (±)-lysergic acid and (±)-LSD] [4], as well as in the regio-and stereocontrolled synthesis of 3-carbamoylcyclopentenones as chiral synthetic intermediates or ligands [5], tetra-(hexa)hydrofuro [3,4-e]isoindol-6-ones as intermediate products in the synthesis of antibiotic lactonamycin [6], and unsaturated γ- [7] and δ-lactams [8].…”
mentioning
confidence: 99%
“…Desilylation of 3-(trimethylsilyl)propynoic acid amides can be performed by the action of bases under mild conditions; this reaction underlies an important preparative procedure for the synthesis of terminal propynamides [6,11,12]. In the presence of Lewis acids tandem processes could occur with formation of C-C bond without isolation of terminal alkynes [13].…”
mentioning
confidence: 99%